2020
DOI: 10.3390/ijms21020453
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Transcriptome Analysis of the ABCB, PIN/PIN-LIKES, and AUX/LAX Families Involved in Somatic Embryogenesis of Lilium pumilum DC. Fisch.

Abstract: Plant cell totipotency is one of the 25 major topics in current scientific research, and somatic embryos are good experimental material for studying cell totipotency. Polar auxin transport plays an important regulatory role in somatic embryogenesis (SE). However, little is known about the auxin transport genes and their regulatory mechanisms in Lilium SE. In this study, we applied single-molecule real-time (SMRT) sequencing to Lilium pumilum DC. Fisch. for the first time and obtained a total of 119,649 transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 99 publications
2
12
0
Order By: Relevance
“…This phenomenon may be explained by very high rate of auxin transport [ 6 ]; hence, the process of exogenous hormone transport into the cells, which is probably determined by LpABCB21 , is not affected. Our previous study demonstrated that LpPILS7 expression level is increased in the light culture, and somatic embryo induction efficiency in the light culture is better than that in the dark culture [ 40 ]. This experiment confirms that LpPILS7 can promote L. pumilum SE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This phenomenon may be explained by very high rate of auxin transport [ 6 ]; hence, the process of exogenous hormone transport into the cells, which is probably determined by LpABCB21 , is not affected. Our previous study demonstrated that LpPILS7 expression level is increased in the light culture, and somatic embryo induction efficiency in the light culture is better than that in the dark culture [ 40 ]. This experiment confirms that LpPILS7 can promote L. pumilum SE.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic transformation method was performed as described previously [ 40 ]. In brief, EC were transferred to somatic embryo induction medium for proliferation and subcultured every 30 days until genetic transformation was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the expression of AUX/IAA transcriptional regulatory genes related to IAA was affected by AUX biosynthesis and signal transduction genes. Auxin and response factors act as transcriptional factors to regulate the expression of auxin response genes by binding to specific sequences of auxin response elements, and they play a role in flower development through transcriptional activation or inhibition [38,39].…”
Section: Comparative Analysis the Expression Of Degs Related To Hormo...mentioning
confidence: 99%